Study on frequency selective characteristics of the microstructure metallic grating in terahertz frequency range based on the hybrid implicit explicit‐pseudospectral time domain method. (23rd December 2014) - Chen, Juan; Wei, Li; Zhang, Anxue; Li, Jianjun
Summary: In this paper, a hybrid implicit explicit‐pseudospectral time domain method is presented to simulate the microstructure metallic grating. The time step size in this method has no relation with the fine spatial discretization, and the spatial discretization along the electrically large direction only needs two cells per wavelength. The three‐dimensional formulas of the method are presented, and the time stability condition of the method is demonstrated. Numerical results show that the memory requirement of the hybrid implicit explicit‐pseudospectral time domain method is reduced by 50% compared with the finite difference time domain method and the computation time is almost 1/40 of that of the finite difference time domain method. Copyright © 2014 John Wiley & Sons, Ltd.